Eksistensi Budaya Sasi Laut Terhadap Pelestarian Ekosistem Mangrove Dan Ekowisata Desa Taar Kota Tual - Kopong, Maria M.; Sukirno, Pradina Anjarwaty; Renjaan, Melissa Justin; Betaubun, Kemilius Deleles; Renjaan, Meiksyana Raynold (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the existence of the